Information Technology Governance in Small and Medium Enterprises - a Systematic Mapping - Silva, Humberto Caetano Cardoso da; Silveira, Denis Silva da; Dornelas, Jairo Simião; Ferreira, Henrique Santos (Journal of Information Systems and Technology Management, 2019)
Information Technology (IT) governance in small and medium-sized businesses is a subject that still requires more effort. Many of the studies that deal with this subject refer to large companies. IT governance structures, originally developed for the context of large enterprises such as COBIT, ISO/IEC 35800 or ITIL, when applied to the context of small and medium enterprises, lead to undesirable results and failures in the deployment process. The objective of this work was to perform a systematic mapping on IT governance mechanisms in small and medium enterprises between 2007 and 2017. Systematic mapping studies are useful for categorizing and summarizing the existing information concerning a research question in an unbiased manner. Thus, from an initial set of 63 papers, a total of 17 research papers were selected for the mapping study. The results obtained allowed us to reach conclusions concerning the state-of-the-art of use of structural and relational mechanisms of IT governance. This allowed us to identify several research gaps, which subsequently provided us with a framework in which new research activities can be more appropriately positioned, and from which useful information for novice usability practitioners can be extracted.